2004
DOI: 10.1143/jjap.43.1848
|View full text |Cite
|
Sign up to set email alerts
|

Halo Ion Implantation Effect on Extension Profile Studied by Scanning Capacitance Microscopy Using All-Metal Probe under FM Control

Abstract: By using an all-metal probe under frequency modulation (FM) control, we developed a scanning capacitance microscope (FM-SCM), and applied it to a study of the halo ion implantation effect on two-dimensional (2D) extension profiles of crosssectional p-channel metal-oxide-semiconductor field effect transistors. With the use of the all-metal probe under FM control, we attain sub-5-nm spatial resolution for the p-n junction in the @C=@V image. The built-in depletion layer presumed by the @C=@V image is narrower fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…STM is one such technique. [6][7][8][9][10] It has already been reported that STM enables the evaluation of the variation in the 2-D carrier profile in the SDE region of the sub-50 nm p-MOSFETs, which is very consistent with the electrical properties of the corresponding transistors. 5) In this study, the 2-D carrier profiles were measured for the embedded monitors in the same chip after the electrical properties of the p-MOSFETs had been measured.…”
Section: -D Carrier Profiles In Sub-50 Nm P-mosfetssupporting
confidence: 60%
“…STM is one such technique. [6][7][8][9][10] It has already been reported that STM enables the evaluation of the variation in the 2-D carrier profile in the SDE region of the sub-50 nm p-MOSFETs, which is very consistent with the electrical properties of the corresponding transistors. 5) In this study, the 2-D carrier profiles were measured for the embedded monitors in the same chip after the electrical properties of the p-MOSFETs had been measured.…”
Section: -D Carrier Profiles In Sub-50 Nm P-mosfetssupporting
confidence: 60%
“…Several two-dimensional (2-D) carrier profiling techniques have been studied as means to evaluate sub-50 nm FETs. [1][2][3][4] It has been reported that we can measure 2-D carrier profiles around SDE regions on the nanometer scale by scanning tunneling microscopy (STM). [5][6][7] We have demonstrated that STM has sufficient spatial resolution to evaluate details in the lateral carrier profiles of the scaled FETs.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed setups of frequency modulation feedback and the capacitance detection technique have been shown elsewhere. 8) We used a sharpened metal wire as a conductive probe and quartz tuning fork (TF) as the force sensor. The capacitance between the probe tip and the sample is modulated twice with the probe oscillation frequency and with the AC self-sensing probe.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…With the use of a self-sensing probe, we have achieved high spatial resolution and sensitivity both in dC=dV and dC=dZ imaging. 8,9) In addition, we can completely eliminate the illumination effect 10) on the capacitance image measurement, because our SCM needs no optical setup. All experiments reported here were carried out in a high vacuum ($10 À4 Pa) environment.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%